The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.marchem.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Chromophoric dissolved organic matter (CDOM) in first-year sea ice in the western Canadian Arctic

Abstract: We monitored the spatiotemporal progression of chromophoric dissolved organic matter (CDOM) in first-year sea ice in the western Canadian Arctic between mid-March and early July 2008. CDOM abundance in bottom ice, as quantified by absorption coefficient at 325 nm, a CDOM (325), showed a positive, linear relationship with the concentration of chlorophyll a, being low at the start of ice algal accumulation, highly enriched during the peak bloom and early post-bloom, and depleted again during sea ice melting. Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 61 publications
7
28
1
Order By: Relevance
“…The sub-surface CDOM absorption maximum (30-120 m) in the EGC area was linked to river and sea-ice brine enriched water, characteristic of the Arctic mixed layer and upper halocline waters and concurs with observations of high CDOM in the EGC and surface waters of the Eurasian Basin (Amon, 2003;Stedmon et al, 2011). Lower absorption in the upper 25-30 m layer in the EGC may reflect the influence of sea-ice melt dilution and photobleaching of CDOM (Granskog et al, 2007Pegau, 2002;Xie et al, 2014). It has been suggested that CDOM incorporated into sea ice can be lost through brine drainage in summer (Xie et al, 2014) as well as photobleaching (Belzile et al, 2000;Xie and Gosselin, 2005).…”
Section: Cdom Absorption In Relation To Water Masses In Fram Straitsupporting
confidence: 81%
See 1 more Smart Citation
“…The sub-surface CDOM absorption maximum (30-120 m) in the EGC area was linked to river and sea-ice brine enriched water, characteristic of the Arctic mixed layer and upper halocline waters and concurs with observations of high CDOM in the EGC and surface waters of the Eurasian Basin (Amon, 2003;Stedmon et al, 2011). Lower absorption in the upper 25-30 m layer in the EGC may reflect the influence of sea-ice melt dilution and photobleaching of CDOM (Granskog et al, 2007Pegau, 2002;Xie et al, 2014). It has been suggested that CDOM incorporated into sea ice can be lost through brine drainage in summer (Xie et al, 2014) as well as photobleaching (Belzile et al, 2000;Xie and Gosselin, 2005).…”
Section: Cdom Absorption In Relation To Water Masses In Fram Straitsupporting
confidence: 81%
“…Lower absorption in the upper 25-30 m layer in the EGC may reflect the influence of sea-ice melt dilution and photobleaching of CDOM (Granskog et al, 2007Pegau, 2002;Xie et al, 2014). It has been suggested that CDOM incorporated into sea ice can be lost through brine drainage in summer (Xie et al, 2014) as well as photobleaching (Belzile et al, 2000;Xie and Gosselin, 2005). Potential dilution of CDOM by sea-ice melt is then contrary to previous works in the Arctic, which suggested that CDOM accumulates in sea-ice during its formation and is subsequently released to surface waters during sea-ice melt providing a source of CDOM to the upper ocean layer (Scully and Miller, 2000).…”
Section: Cdom Absorption In Relation To Water Masses In Fram Straitmentioning
confidence: 99%
“…The vertical distribution of averaged Tchla values have resembled a L‐shape, as shown in Figure c, similar to those reported by Xie et al . [] and Hill and Zimmerman []. Tchla was very low in the upper parts of the ice (Figure c and Table ).…”
Section: Resultsmentioning
confidence: 97%
“…Particulate absorption in Arctic sea ice has been studied very sparsely [ Mundy et al ., ]. Investigations focused on CDOM in sea ice during different stages of its formation [e.g., Müller et al ., ; Xie et al ., ; Logvinova et al ., ; Hill and Zimmerman , ]. It has been documented that CDOM absorption was in most cases enriched (relative to salinity) compared to underlying water [e.g., Müller et al ., ]; its values were elevated in the bottom of the ice and ice algae significantly contributed to CDOM accumulation [e.g., Xie et al ., ; Granskog et al ., ; Hill and Zimmerman , ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to characterize the spatial and temporal CDOM variations in aquatic environments, spectral analysis of CDOM (absorption and fl uorescence) can trace its origin and chemical composition [26][27]. Based on the characteristics of the absorption spectrum, spectral indices (e.g., absorption coeffi cient at specifi c wavelength), absorption ratio (E 250:365 ), spectral slopes (S, S 275-295 and S 350-400 ), the ratio of S 275-295 and S 350-400 , and SUVA 254 values have been developed to trace DOM source, molecular size, and aromatic hydrocarbon content, etc.…”
Section: Introductionmentioning
confidence: 99%